Resin composition

JP7639869B2Active Publication Date: 2025-03-05AJINOMOTO CO INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023167775
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-11-22
Filing Date
2023-09-28
Publication Date
2025-03-05
Estimated Expiration
2043-09-28

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、樹脂成分のバイオマス比率を高くしても、ピール強度が高く、絶縁信頼性に優れる硬化物をもたらす樹脂組成物;前記樹脂組成物を含む樹脂組成物層を備える樹脂シート;前記樹脂組成物の硬化物で形成された絶縁層を含むプリント配線板;並びに、前記プリント配線板を含む半導体装置;を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639869000001
    Figure 0007639869000001
  • Figure 0007639869000002
    Figure 0007639869000002
  • Figure 0007639869000003
    Figure 0007639869000003
Patent Text Reader

Abstract

To provide a resin composition or the like which gives a cured product having high peel strength and excellent insulation reliability even when the biomass ratio of a resin component is increased.SOLUTION: The resin composition contains (A) a thermosetting resin and (B) a thermoplastic resin. The content of the component (A) is 10 mass% or more based on 100 mass% of a nonvolatile component in the resin composition. The content of the component (B) is 10 mass% or less based on 100 mass% of the nonvolatile component in the resin composition. The biomass ratio of a resin component in the resin composition is 5 mass% or more. The biomass ratio of a liquid resin in the resin component is 40 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. The present invention further relates to a resin sheet, a printed wiring board, and a semiconductor device obtained by using the resin composition. [Background technology]

[0002] A printed wiring board is generally provided with an insulating layer, which is formed by curing a resin composition. As such a resin composition, for example, the resin composition disclosed in Patent Document 1 is known. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-66792 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, from the viewpoints of environmental protection and carbon neutrality, there has been a demand for insulating layers with a high biomass ratio.

[0005] However, when an insulating layer is formed using a resin composition in which the biomass ratio is increased by using a resin component derived from biomass, the peel strength between the insulating layer and the conductor layer may decrease, and the insulating reliability may be deteriorated.

[0006] The present invention has been devised in view of the above-mentioned problems, and has an object to provide: a resin composition which provides a cured product having high peel strength and excellent insulation reliability even when the biomass ratio of the resin component in the resin composition is increased; a resin sheet including a resin composition layer which includes the resin composition; a printed wiring board which includes an insulating layer formed from a cured product of the resin composition; and a semiconductor device which includes the printed wiring board. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have found that when the biomass ratio of the resin components including (A) a thermosetting resin and (B) a thermoplastic resin is increased, the peel strength is decreased and the insulation reliability is deteriorated. Although this does not limit the technical scope of the present invention, it is presumed that the above-mentioned decrease in peel strength and the decrease in insulation reliability occur because the resin components derived from biomass can unavoidably contain impurities and the resin components derived from biomass tend to have a relatively flexible molecular structure because they exist in the living body. As a result of intensive research to solve the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved even if the biomass ratio of the resin components is increased by adjusting the contents of the (A) and (B) components to be within a predetermined range and adjusting the (A) and (B) components so that the biomass ratio of the liquid resin in the resin components is 40 mass% or less, and have completed the present invention.

[0008] That is, the present invention includes the following. [1] (A) Thermosetting resins, and (B) A resin composition containing a thermoplastic resin, The content of the (A) component is 10% by mass or more when the total amount of non-volatile components in the resin composition is 100% by mass, The content of the (B) component is 10% by mass or less when the total amount of non-volatile components in the resin composition is 100% by mass, The biomass ratio of the resin component in the resin composition is 5% by mass or more, A resin composition, wherein a biomass ratio of a liquid resin in a resin component is 40 mass% or less. [2] The resin composition according to [1], further comprising (C) an inorganic filler. [3] The resin composition according to [2], wherein the content of the inorganic filler (C) is 20 mass% or more, when the non-volatile components in the resin composition are 100 mass%. [4] The resin composition according to any one of [1] to [3], wherein the thermosetting resin (A) contains an epoxy resin (A-1). [5] The resin composition according to any one of [1] to [4], wherein the thermosetting resin (A) contains a curing agent (A-2). [6] The resin composition according to any one of [1] to [5], wherein the liquid resin contains either (A-1) an epoxy resin or (A-2) a curing agent. [7] The resin composition according to any one of [1] to [6], which is for forming an insulating layer. [8] A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of [1] to [7]. [9] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [7].

[10] A semiconductor device comprising the printed wiring board described in [9]. Effect of the Invention

[0009] According to the present invention, it is possible to provide a resin composition which provides a cured product having high peel strength and excellent insulation reliability even when the biomass ratio of the resin component is increased; a resin sheet including a resin composition layer including the resin composition; a printed wiring board including an insulating layer formed from a cured product of the resin composition; and a semiconductor device including the printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0011] In this specification, the term "non-volatile components" refers to all non-volatile components in the resin composition excluding the solvent, unless otherwise specified. The term "resin components" refers to non-volatile components in the resin composition excluding the inorganic filler (C) described below, unless otherwise specified. The term "liquid resin" refers to a resin that is liquid at a temperature of 20°C.

[0012] [Resin composition] The resin composition of the present invention is a resin composition containing (A) a thermosetting resin and (B) a thermoplastic resin, wherein the content of component (A) is 10 mass% or more when the nonvolatile components in the resin composition are taken as 100 mass%, the content of component (B) is 10 mass% or less when the nonvolatile components in the resin composition are taken as 100 mass%, the biomass ratio of the resin components in the resin composition is 5 mass% or more, and the biomass ratio of liquid resin in the resin components is 40 mass% or less.

[0013] As described above, the present inventors have found, as a result of intensive research, that when the biomass ratio of the resin component containing the (A) component and the (B) component is increased, the peel strength is decreased and the insulation reliability is deteriorated. Furthermore, as a result of further intensive research, the present inventors have found that when the biomass ratio of the liquid resin in the resin component containing the (A) component and the (B) component is increased, the peel strength is further decreased and the insulation reliability is further deteriorated. In the resin composition of the present invention, the contents of the (A) component and the (B) component are adjusted to be 10% by mass or more and 10% by mass or less, respectively, when the non-volatile components in the resin composition are taken as 100% by mass, and the (A) component and the (B) component are adjusted so that the biomass ratio of the liquid resin in the resin component is low, that is, 40% by mass or less, thereby making it possible to obtain a cured product with high peel strength and excellent insulation reliability even if the biomass ratio of the entire resin components is increased to 5% by mass or more. In addition, even if the biomass ratio of the entire resin component is increased to 5 mass% or more, it is possible to obtain a cured product with high peel strength and excellent insulation reliability, so it is also possible to obtain a cured product with a high biomass ratio in the entire resin composition.Furthermore, it is usually possible to obtain a cured product with excellent lamination properties.

[0014] The biomass ratio of the resin component in the resin composition is 5% by mass or more, preferably 5.5% by mass or more, and more preferably 6% by mass or more. There is no particular upper limit, but it may be 100% by mass or less. The biomass ratio can be calculated by the method described in the examples below. Even if the resin composition contains a resin component that has been certified by the mass balance method, the biomass ratio of the resin component in the resin composition is calculated by the method described in the examples below.

[0015] The biomass ratio of the liquid resin in the resin component is 40% by mass or less, preferably 35% by mass or less, more preferably 30% by mass or less, and even more preferably 25% by mass or less, from the viewpoint of obtaining the effects of the present invention significantly. The lower limit is not particularly limited, but it may be 0% by mass or more. The biomass ratio of the liquid resin in the resin component can be calculated by the method described in the examples below. When the resin component contains multiple liquid resins, the biomass ratio of the liquid resin in the resin component may be within this range. Even when the resin composition contains a liquid resin certified by the mass balance method, the biomass ratio of the liquid resin in the resin component is calculated by the method described in the examples below.

[0016] The resin composition may contain (A) a thermosetting resin and (B) a thermoplastic resin in combination with (C) an inorganic filler and (D) other additives. Each component contained in the resin composition will be described below.

[0017] <(A) Thermosetting resin> The resin composition of the present invention contains a thermosetting resin (A) as the component (A). The type of the thermosetting resin (A) is not particularly limited as long as it can be thermally cured. The thermosetting resin (A) may be used alone or in combination of two or more types.

[0018] As the (A) thermosetting resin, a thermosetting resin used in forming an insulating layer of a printed wiring board can be used. Therefore, one embodiment of the resin composition contains either (A-1) an epoxy resin or (A-2) a curing agent as the (A) thermosetting resin. The (A) thermosetting resin may further contain (A-3) a radical polymerizable resin and (A-4) a curing accelerator, as necessary.

[0019] -(A-1) Epoxy resin- The (A-1) epoxy resin is a thermosetting resin having an epoxy group. The epoxy resin may be an epoxy resin derived from a fossil resource, or may be an epoxy resin derived from biomass. The (A-1) epoxy resin may be used alone or in combination of two or more kinds.

[0020] Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, and the like. Examples of epoxy resins include phenol aralkyl type epoxy resins, biphenyl type epoxy resins, aliphatic epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, phenolphthalimidine type epoxy resins, epoxidized soybean oil, cashew modified epoxy resins, epoxidized cardanol resins, etc. Epoxidized soybean oil refers to an epoxy resin in which all or part of the unsaturated bonds of soybean oil have been epoxidized, cashew modified epoxy resin refers to an epoxy resin modified using cashew oil, and epoxidized cardanol resin refers to an epoxy resin in which all or part of the cardanol resin has been epoxidized.

[0021] The epoxy resin preferably has two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more, based on 100% by mass of the non-volatile components of the epoxy resin.

[0022] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only liquid epoxy resins as the epoxy resin, or may contain only solid epoxy resins, or may contain a combination of liquid epoxy resins and solid epoxy resins.

[0023] The resin composition may contain, as the epoxy resin, only an epoxy resin derived from a fossil resource, or only an epoxy resin derived from a biomass, or may contain a combination of an epoxy resin derived from a fossil resource and an epoxy resin derived from a biomass. Also, the resin composition may contain, as the epoxy resin, only a solid epoxy resin derived from a fossil resource, or may contain a combination of a solid epoxy resin derived from a fossil resource and a liquid epoxy resin derived from a biomass.

[0024] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule, and is preferably a liquid epoxy resin derived from biomass.

[0025] Preferred liquid epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, epoxy resins having a butadiene structure, aliphatic epoxy resins, epoxidized soybean oil, cashew modified epoxy resins, and epoxidized cardanol resins, and more preferred are bisphenol A type epoxy resins, aliphatic epoxy resins, epoxidized soybean oil, cashew modified epoxy resins, and epoxidized cardanol resins.

[0026] Specific examples of liquid epoxy resins derived from fossil resources include DIC's "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins); Mitsubishi Chemical's "828US", "828EL", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins); Mitsubishi Chemical's "jER807" and "1750" (bisphenol F type epoxy resins); Mitsubishi Chemical's "jER152" (phenol novolac type epoxy resin); Mitsubishi Chemical's "630", "630LSD", and "604" (glycidylamine type epoxy resins); ADEKA's "ED-523T" (glycirol type epoxy resin); ADEKA's "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resins). amine type epoxy resin); ADEKA's "EP-4088S" (dicyclopentadiene type epoxy resin); Nippon Steel Chemical & Material Co., Ltd.'s "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); Nagase ChemteX's "EX-721" (glycidyl ester type epoxy resin); Daicel's "Celloxide 2021P" (alicyclic epoxy resin with an ester skeleton); Daicel's "PB-3600", Nippon Soda's "JP-100" and "JP-200" (epoxy resin with a butadiene structure (epoxidized polybutadiene resin)); Nippon Steel Chemical & Material's "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin), etc.

[0027] Specific examples of liquid epoxy resins derived from biomass include "Denacol EX-521" (aliphatic epoxy resin) manufactured by Nagase ChemteX Corporation, "Sanso Cizer E-2000H" (epoxidized soybean oil) manufactured by New Japan Chemical Co., Ltd., "LITE 514SE" (cashew-modified epoxy resin) manufactured by Cardolite Corporation, and "FE-5130" (epoxidized cardanol resin) manufactured by Tohoku Kako Co., Ltd.

[0028] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0029] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, naphthol novolac type epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, phenol aralkyl type epoxy resin, tetraphenylethane type epoxy resin, and phenolphthalimidine type epoxy resin are preferred, and biphenyl type epoxy resin and naphthylene ether type epoxy resin are more preferred.

[0030] Specific examples of solid epoxy resins derived from fossil resources include DIC's "HP4032H" (naphthalene type epoxy resin); DIC's "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins); DIC's "N-690" (cresol novolac type epoxy resin); DIC's "N-695" (cresol novolac type epoxy resin); DIC's "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resin); and DIC's "EXA- 7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V", ESN4100V (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd. Examples of epoxy resins include "YX7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YX7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.

[0031] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably 1:0.01 to 1:20, more preferably 1:0.05 to 1:10, and particularly preferably 1:0.1 to 1:7.

[0032] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 3,000 g / eq., further preferably 80 g / eq. to 2,000 g / eq., and particularly preferably 110 g / eq. to 1,000 g / eq. The epoxy equivalent represents the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0033] The weight average molecular weight (Mw) of the epoxy resin is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0034] From the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability, the content of the epoxy resin as component (A-1) is preferably 1 mass % or more, more preferably 5 mass % or more, and particularly preferably 10 mass % or more, and is preferably 45 mass % or less, more preferably 40 mass % or less, and particularly preferably 35 mass % or less, based on 100 mass % of the non-volatile components in the resin composition.

[0035] In the present invention, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are taken as 100 mass %, unless otherwise specified.

[0036] The content of the liquid epoxy resin contained in the component (A-1) is preferably 0% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, and preferably 10% by mass or less, more preferably 9% by mass or less, and even more preferably 8% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining the effects of the present invention prominently. The content of the biomass-derived liquid epoxy resin contained in the component (A-1) is preferably 0% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, and preferably 10% by mass or less, more preferably 9% by mass or less, and even more preferably 8% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining the effects of the present invention prominently.

[0037] From the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability, the content of the solid epoxy resin in the component (A-1) is preferably 1 mass % or more, more preferably 3 mass % or more, and particularly preferably 5 mass % or more, and is preferably 45 mass % or less, more preferably 40 mass % or less, and particularly preferably 30 mass % or less, based on 100 mass % of the non-volatile components in the resin composition.

[0038] From the viewpoint of significantly obtaining the effects of the present invention, the biomass ratio of the epoxy resin contained in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The biomass ratio can be calculated by the method described in the examples described later.

[0039] -(A-2) Hardener- The (A-2) curing agent is a thermosetting resin having a function of reacting with the (A-1) component to cure the resin composition. The (A-2) curing agent as the (A-2) component does not include those corresponding to the above-mentioned (A-1) component. The curing agent may be a curing agent derived from fossil resources, or may be a curing agent derived from biomass. The (A-2) curing agent may be used alone or in combination of two or more types.

[0040] Examples of the (A-2) curing agent include active ester curing agents, phenolic curing agents, naphthol curing agents, benzoxazine curing agents, cyanate ester curing agents, carbodiimide curing agents, etc. Among them, from the viewpoint of obtaining the effects of the present invention remarkably, it is preferable that the (A-2) component contains at least one of active ester curing agents, phenolic curing agents, naphthol curing agents, and benzoxazine curing agents.

[0041] The (A-2) curing agent includes a liquid curing agent that is liquid at a temperature of 20° C. (hereinafter sometimes referred to as a "liquid curing agent") and a curing agent that is solid at a temperature of 20° C. (hereinafter sometimes referred to as a "solid curing agent") The resin composition may contain only a liquid curing agent as the curing agent, or may contain only a solid curing agent, or may contain a combination of a liquid curing agent and a solid curing agent.

[0042] The curing agent may be a curing agent derived from a fossil resource or may be a curing agent derived from a biomass, but from the viewpoint of obtaining the effects of the present invention significantly, it is preferable to include a curing agent derived from a biomass, and a combination of a curing agent derived from a fossil resource and a curing agent derived from a biomass is preferable. In addition, the resin composition may contain a combination of a solid curing agent derived from a fossil resource and a solid curing agent derived from a biomass, or may contain a liquid curing agent derived from a biomass, a solid curing agent derived from a fossil resource, and a solid curing agent derived from a biomass in combination.

[0043] The active ester-based curing agent is preferably a solid curing agent, and in particular, a solid curing agent derived from biomass is preferable.

[0044] The active ester curing agent is not particularly limited, but generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, esters of heterocyclic hydroxy compounds, esters having a furan skeleton with carbonyl groups bonded to the 2nd and 5th positions, and esters having a thiophene skeleton with carbonyl groups bonded to the 2nd and 5th positions, are preferably used. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and furandicarboxylic acid. Examples of the phenol compound or naphthol compound include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, hexestrol, daidzein, equol, curcumin, phenol, o-cresol, m-cresol, p-cresol, cardanol, eugenol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, resveratrol, 3,4'-dihydroxyflavone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-phenol polyadducts and other dicyclopentadiene-type diphenol compounds, and phenol novolak. Here, the term "dicyclopentadiene type diphenol compound" refers to a diphenol compound obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0045] Specifically, an active ester-based curing agent having a furan skeleton with carbonyl groups bonded to the 2- and 5-positions, an active ester-based curing agent having a thiophene skeleton with carbonyl groups bonded to the 2- and 5-positions, an active ester-based curing agent containing a dicyclopentadiene-type diphenol structure, an active ester-based curing agent containing a naphthalene structure, an active ester-based curing agent containing an acetylated product of phenol novolac, and an active ester-based curing agent containing a benzoylated product of phenol novolac are preferred, among which an active ester-based curing agent having a furan skeleton with carbonyl groups bonded to the 2- and 5-positions, an active ester-based curing agent having a thiophene skeleton with carbonyl groups bonded to the 2- and 5-positions, and an active ester-based curing agent having a furan skeleton with carbonyl groups bonded to the 2- and 5-positions are more preferred, and an active ester-based curing agent having a furan skeleton with carbonyl groups bonded to the 2- and 5-positions is even more preferred. In addition, an active ester-based curing agent having a furan skeleton with carbonyl groups bonded to the 2- and 5-positions, and an active ester-based curing agent having a thiophene skeleton with carbonyl groups bonded to the 2- and 5-positions are preferably solid curing agents derived from biomass. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0046] The active ester-based curing agent can be obtained, for example, by condensation reaction of a hydroxyl-containing aromatic compound having an aromatic hydroxyl group, a dicarboxylic acid halide, and a divalent phenol compound. For example, a biomass-derived active ester-based curing agent can be obtained by using a dicarboxylic acid halide having a furan skeleton or a thiophene skeleton derived from any biomass such as plant-derived glucose, plant-derived cellulose, and plant-derived fructose as the dicarboxylic acid halide.

[0047] Commercially available active ester curing agents derived from fossil resources include active ester compounds containing a dicyclopentadiene-type diphenol structure such as "EXB-9451", "EXB-9460", "EXB-9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "HPC-8000L-65TM" (manufactured by DIC Corporation), active ester compounds containing a naphthalene structure such as "EXB-9416-70BK", "EXB-8100L-65T", "EXB-8150-65T", "EXB-8150L-65T", "HPC-8150-60T", "HPC-8150-62T", and "HP-B-8151-62T" (manufactured by DIC Corporation), and phenol novo curing agents such as "EXB-9452", "EXB-9451", "EXB-9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "HPC-8000L-65TM" (manufactured by DIC Corporation). Examples of active ester compounds containing acetylated phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation), active ester compounds containing benzoylated phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), active ester curing agents which are acetylated phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation), active ester curing agents which are benzoylated phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group includes "PC1300-02-65MA" (manufactured by Air Water Corporation).

[0048] The phenol-based hardener and naphthol-based hardener are preferably solid hardeners, and the solid hardener may be either a solid hardener derived from a fossil resource or a solid hardener derived from a biomass.

[0049] As the phenol-based curing agent and naphthol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure or a naphthol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of obtaining the effect of the present invention remarkably, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable.

[0050] Specific examples of phenol-based curing agents derived from fossil resources and naphthol-based curing agents derived from fossil resources include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel Chemical & Material Co., Ltd., and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA3018-50P", "EXB-9500", and "KA-1163" manufactured by DIC Corporation.

[0051] A specific example of a biomass-derived phenol-based curing agent is tannic acid manufactured by Sumitomo Pharma Food & Chemical Co., Ltd.

[0052] The benzoxazine-based curing agent is preferably a liquid curing agent, and more preferably a biomass-derived liquid curing agent.

[0053] Specific examples of benzoxazine-based curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0054] A specific example of a liquid benzoxazine-based hardener derived from biomass is "CR-276" manufactured by Tohoku Kako Co., Ltd.

[0055] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0056] The carbodiimide curing agent is a compound having one or more carbodiimide groups (-N=C=N-) in one molecule, and the carbodiimide curing agent is preferably a compound having two or more carbodiimide groups in one molecule.

[0057] Specific examples of the carbodiimide-based curing agent include commercially available carbodiimide-based curing agents such as Carbodilite V-03 (carbodiimide group equivalent: 216, V-05 (carbodiimide group equivalent: 262), V-07 (carbodiimide group equivalent: 200), V-09 (carbodiimide group equivalent: 200), and Stavaxol P (carbodiimide group equivalent: 302), all manufactured by Nisshinbo Chemical Co., Ltd.

[0058] The ratio of the amount of the epoxy resin (A-1) to the component (A-2) is preferably 1:0.01 to 1:5, more preferably 1:0.3 to 1:3, and even more preferably 1:0.5 to 1:2, in terms of the ratio of [total number of epoxy groups in the epoxy resin (A-1)]:[total number of active groups in the component (A-2)]. Here, the "number of epoxy groups in the epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition by the epoxy equivalent. In addition, the "number of active groups in the component (A-2)" refers to the total value obtained by dividing the mass of the non-volatile components of the component (A-2) present in the resin composition by the active group equivalent. By setting the ratio of the amount of the epoxy resin to the component (A-2) within this range, the effects of the present invention can be obtained significantly.

[0059] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of the (A-2) component is preferably 1% by mass or more, more preferably 3% by mass or more, and more preferably 5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer. The upper limit is preferably 35% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less, and 10% by mass or less.

[0060] The content of the liquid curing agent is preferably 1% by mass or more, more preferably 1.5% by mass or more, and more preferably 3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, from the viewpoint of obtaining the desired effects of the present invention remarkably. The upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, and more preferably 10% by mass or less. The content of the biomass-derived liquid curing agent contained in the (A-2) component is preferably 1% by mass or more, more preferably 1.5% by mass or more, and more preferably 3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining the effects of the present invention remarkably. The upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, and more preferably 10% by mass or less.

[0061] The content of the solid curing agent is preferably 1% by mass or more, more preferably 2% by mass or more, and more preferably 3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, from the viewpoint of obtaining the desired effects of the present invention remarkably. The upper limit is preferably 25% by mass or less, more preferably 23% by mass or less, more preferably 20% by mass or less, and 10% by mass or less. The content of the biomass-derived solid curing agent contained in the (A-2) component is preferably 1% by mass or more, more preferably 1.5% by mass or more, and more preferably 3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining the effects of the present invention remarkably. The upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, and more preferably 10% by mass or less.

[0062] -(A-3) Radical polymerizable resin- The (A-3) radical polymerizable resin is a thermosetting resin that contains a radical polymerizable unsaturated group, and when the resin composition is heated, the (A-3) radical polymerizable resin reacts with the thermal radicals generated by the heating to obtain a cured product. The (A-3) radical polymerizable resin as the (A-3) component does not include those that correspond to the above-mentioned (A-1) component and (A-2) component. The (A-3) radical polymerizable resin may be used alone or in combination of two or more types.

[0063] The resin composition may contain, as the radical polymerizable resin, a radical polymerizable resin derived from a fossil resource or a radical polymerizable resin derived from biomass. However, from the viewpoint of obtaining the effects of the present invention significantly, it is preferable that the resin composition contains only a radical polymerizable resin derived from biomass.

[0064] The type of radical polymerizable resin is not particularly limited as long as it has one or more (preferably two or more) radical polymerizable unsaturated groups in one molecule. Examples of the radical polymerizable resin include resins having one or more radical polymerizable unsaturated groups selected from maleimide group, vinyl group, allyl group, styryl group, vinylphenyl group, acryloyl group, methacryloyl group, fumaroyl group, maleoyl group, and propenyl group. Among them, from the viewpoint of obtaining the effect of the present invention remarkably, the radical polymerizable resin is preferably one or more selected from maleimide resin, (meth)acrylic resin, allyl resin, and styryl resin, and more preferably either (meth)acrylic resin or allyl resin.

[0065] The radical polymerizable resin includes a liquid radical polymerizable resin that is liquid at a temperature of 20° C. (hereinafter, sometimes referred to as a "liquid radical polymerizable resin") and a radical polymerizable resin that is solid at a temperature of 20° C. (hereinafter, sometimes referred to as a "solid radical polymerizable resin"). The resin composition may contain only a liquid radical polymerizable resin as the radical polymerizable resin, or may contain only a solid radical polymerizable resin, or may contain a combination of a liquid radical polymerizable resin and a solid radical polymerizable resin, but from the viewpoint of significantly obtaining the effects of the present invention, it is preferable to contain only a liquid radical polymerizable resin.

[0066] The (meth)acrylic resin is not particularly limited in type, and may be a monomer or an oligomer, so long as it has one or more (preferably two or more) (meth)acryloyl groups in one molecule. Here, the term "(meth)acryloyl group" is a general term for acryloyl groups and methacryloyl groups.

[0067] Examples of (meth)acrylic resins derived from fossil resources include (meth)acrylate monomers, as well as (meth)acrylic resins such as "A-DOG" (manufactured by Shin-Nakamura Chemical Co., Ltd.), "DCP-A" (manufactured by Kyoeisha Chemical Co., Ltd.), "NPDGA", "FM-400", "R-687", "THE-330", "PET-30", and "DPHA" (all manufactured by Nippon Kayaku Co., Ltd.). "(Meth)acrylate" is a term that includes methacrylate, acrylate, and combinations thereof.

[0068] An example of a biomass-derived (meth)acrylic resin is ARONIX M-930 (manufactured by Toagosei Co., Ltd.).

[0069] The allyl resin is not particularly limited in type as long as it has one or more allyl groups in one molecule, and may be a monomer or an oligomer. An example of an allyl resin derived from biomass is β-carotene.

[0070] There is no particular limitation on the type of maleimide resin, so long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl groups) in one molecule. Examples of maleimide resins include (1) maleimide resins having an aliphatic skeleton (preferably an aliphatic skeleton having 36 carbon atoms derived from dimer diamine), such as "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all manufactured by DigiCner Molecules), and "SLK6895-T90" (manufactured by Shin-Etsu Chemical Co., Ltd.); (2) maleimide resins having an indane skeleton, as described in the Japan Institute of Invention and Innovation Disclosure Technical Bulletin No. 2020-500211; and (3) maleimide resins having an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000" (manufactured by Daiwa Kasei Co., Ltd.), and "BMI-80" (manufactured by Keiai Kasei Co., Ltd.).

[0071] The styryl resin is not particularly limited in type, and may be a monomer or oligomer, as long as it has one or more (preferably two or more) styryl groups or vinylphenyl groups in one molecule. Examples of the styryl resin include styrene monomers, as well as styryl resins such as "OPE-2St", "OPE-2St 1200", and "OPE-2St 2200" (all manufactured by Mitsubishi Gas Chemical Company, Inc.).

[0072] From the viewpoint of obtaining the effects of the present invention prominently, the content of the radical polymerizable resin is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0073] The content of the liquid radical polymerizable resin is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, and preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3.5% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining the effects of the present invention significantly. The content of the biomass-derived liquid radical polymerizable resin contained in the thermosetting resin is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, and preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3.5% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining the effects of the present invention significantly.

[0074] -(A-4) Curing accelerator- The (A-4) curing accelerator is a thermosetting resin that functions as a curing catalyst to accelerate the curing of the (A-1) epoxy resin. The (A-4) curing accelerator may be a curing accelerator derived from fossil resources or a curing accelerator derived from biomass. The (A-4) curing accelerator as the (A-4) component does not include those that fall under the above-mentioned (A-1) to (A-3) components.

[0075] As the (A-4) curing accelerator, a compound that accelerates the curing of the epoxy resin can be used. Examples of such (A-4) curing accelerators include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. As the (A-4) curing accelerator, one type may be used alone, or two or more types may be used in combination.

[0076] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0077] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0078] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0079] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0080] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0081] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0082] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (A-4) curing accelerator is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.03% by mass or more, and is preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0083] From the viewpoint of obtaining the effects of the present invention remarkably, the content of the (A) thermosetting resin is 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, 40% by mass or less, or 30% by mass or less.

[0084] From the viewpoint of significantly obtaining the effects of the present invention, all of the liquid resins contained as the (A) thermosetting resin are preferably at least one of (A-1) an epoxy resin, (A-2) a curing agent, and (A-3) a radically polymerizable resin, and more preferably at least one of (A-1) an epoxy resin, and (A-2) a curing agent.

[0085] From the viewpoint of obtaining the effects of the present invention prominently, the content of all liquid resins in the (A) thermosetting resin is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, relative to 100% by mass of non-volatile components in the resin composition, and is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more.

[0086] From the viewpoint of obtaining the remarkable effects of the present invention, the biomass ratio of the entire thermosetting resin (A) is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. The biomass ratio can be calculated by the method described in the examples below.

[0087] <(B) Thermoplastic resin> The resin composition of the present invention contains a thermoplastic resin (B) as the component (B). The thermoplastic resin (B) as the component (B) does not include those corresponding to the above-mentioned component (A). The thermoplastic resin (B) may be used alone or in combination of two or more kinds.

[0088] (B) Thermoplastic resins include thermoplastic resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid thermoplastic resins") and thermoplastic resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid thermoplastic resins"). The resin composition may contain only liquid thermoplastic resins as thermoplastic resins, or may contain only solid thermoplastic resins, or may contain a combination of liquid thermoplastic resins and solid thermoplastic resins. From the viewpoint of significantly obtaining the effects of the present invention, it is preferable that the resin composition contains only solid thermoplastic resins.

[0089] The resin composition may contain, as the thermoplastic resin (B), a thermoplastic resin derived from a fossil resource, or may contain a thermoplastic resin derived from a biomass. Also, the resin composition may contain, as the thermoplastic resin (B), only a solid thermoplastic resin derived from a fossil resource, only a solid thermoplastic resin derived from a biomass, or a combination of a solid thermoplastic resin derived from a fossil resource and a solid thermoplastic resin derived from a biomass.

[0090] The resin composition may contain, as the (B) thermoplastic resin, a particulate thermoplastic resin that maintains the particulate form in the resin composition, or a non-particulate thermoplastic resin that is mixed or dissolved in the resin composition. Among these, the resin composition preferably contains a non-particulate thermoplastic resin from the viewpoint of obtaining the effects of the present invention significantly.

[0091] Examples of non-particulate thermoplastic resins include polyimide resins, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polybutadiene resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyetheretherketone resins, polyester resins, and polyamide resins. In one embodiment, the (B) thermoplastic resin preferably contains a thermoplastic resin selected from the group consisting of polyimide resins and phenoxy resins, and more preferably contains a phenoxy resin. The thermoplastic resin may be used alone or in combination of two or more types.

[0092] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0093] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0094] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.

[0095] Examples of polyvinyl acetal resins include polyvinyl formal resins and polyvinyl butyral resins, and polyvinyl butyral resins are preferred.Specific examples of polyvinyl acetal resins include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denka Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0096] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0097] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.

[0098] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0099] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0100] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0101] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.

[0102] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include Mitsubishi Gas Chemical's "FPC0220," Asahi Kasei Chemical's "T6002" and "T6001" (polycarbonate diols), and Kuraray's "C-1090," "C-2090," and "C-3090" (polycarbonate diols). Specific examples of polyether ether ketone resins include Sumitomo Chemical's "Sumiploy K."

[0103] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.

[0104] Examples of polyamide resins include nylon 6 and nylon 66. The polyamide resin is preferably a polyamide resin derived from biomass. Examples of polyamide resins derived from biomass include "Vegichem Green V335" manufactured by Tsuno Food Industry Co., Ltd.

[0105] Examples of particulate thermoplastic resins include rubber particles, polyamide fine particles, and silicone particles, with rubber particles being preferred.

[0106] As the rubber particles, commercially available products may be used, for example, "EXL2655" manufactured by Dow Chemical Japan, "AC3401N" and "AC3816N" manufactured by Aica Kogyo Co., Ltd.

[0107] The weight average molecular weight (Mw) of the thermoplastic resin (B) is, from the viewpoint of significantly obtaining the effects of the present invention, preferably 5,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 50,000 or less.

[0108] As another embodiment of the thermoplastic resin (B), the thermoplastic resin (B) may be an elastomer. The thermoplastic elastomer is a resin having flexibility, and is preferably a resin having rubber elasticity or a resin exhibiting rubber elasticity by being polymerized with other components. The elastomer may be used alone or in combination of two or more kinds.

[0109] An example of a resin having rubber elasticity is a resin that exhibits an elastic modulus of 1 GPa or less when a tensile test is carried out at a temperature of 25° C. and a humidity of 40% RH in accordance with Japanese Industrial Standards (JIS K7161).

[0110] The elastomer may be an elastomer derived from fossil resources or may be an elastomer derived from biomass.

[0111] The elastomer preferably has a high molecular weight. The number average molecular weight (Mn) of the elastomer is preferably 1,000 or more, more preferably 1,500 or more, even more preferably 2,000 or more, even more preferably 3,000 or more, and particularly preferably 5,000 or more. The upper limit is preferably 1,000,000 or less, more preferably 900,000 or less. The number average molecular weight (Mn) is a number average molecular weight in terms of polystyrene measured using GPC (gel permeation chromatography).

[0112] The elastomer is preferably one or more selected from resins having a glass transition temperature (Tg) of 25° C. or less and resins that are liquid at 25° C. or less. The glass transition temperature of the resin having a glass transition temperature (Tg) of 25° C. or less is preferably 20° C. or less, more preferably 15° C. or less. The lower limit of the glass transition temperature is not particularly limited, but it can usually be −15° C. or more. The resin that is liquid at 25° C. is preferably a resin that is liquid at 20° C. or less, more preferably a resin that is liquid at 15° C. or less. The glass transition temperature can be measured by DSC (differential scanning calorimetry) at a heating rate of 5° C. / min.

[0113] As the elastomer, a resin having one or more structures selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polycarbonate structure, and a polystyrene structure in the molecule is preferred. Among them, a resin having one or more structures selected from a polybutadiene structure, a poly(meth)acrylate structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polycarbonate structure, and a polystyrene structure is more preferred. Furthermore, a resin having one or more structures selected from a polybutadiene structure and a polyalkyleneoxy structure is more preferred, and a resin having a polybutadiene structure is particularly preferred. "(Meth)acrylate" is a term that includes methacrylate, acrylate, and a combination thereof. These structures may be included in the main chain or in the side chain.

[0114] The elastomer may have a functional group capable of reacting with the epoxy resin (A-1). When the elastomer reacts with the epoxy resin (A-1), the mechanical strength of the cured product of the resin composition can be increased. The functional group capable of reacting with the epoxy resin (A-1) includes a functional group that appears by heating. The functional group capable of reacting with the epoxy resin (A-1) is, for example, one or more functional groups selected from the group consisting of a hydroxy group, a carboxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, a urethane group, and a maleimide group. Among them, the functional group is preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, a urethane group, or a maleimide group, more preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, or a maleimide group, and particularly preferably a phenolic hydroxyl group or a maleimide group. However, the functional group is included. The number average molecular weight (Mn) of the elastomer is preferably 3,000 or more.

[0115] An example of the elastomer is a resin containing a polybutadiene structure. The polybutadiene structure may be contained in the main chain or in a side chain. The polybutadiene structure may be partially or entirely hydrogenated. A resin containing a polybutadiene structure is sometimes called a "polybutadiene resin." Specific examples of polybutadiene resins include "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", and "Ricon 184MA6" (polybutadiene containing an acid anhydride group) manufactured by Cray Valley Corporation; "GQ-1000" (polybutadiene having hydroxyl and carboxyl groups introduced therein), "G-1000", "G-2000", and "G-3000" (polybutadiene having hydroxyl groups at both ends), "GI-1000", "GI-2000", and "GI-3000" (polybutadiene having hydrogenated hydroxyl groups at both ends) manufactured by Nippon Soda Co., Ltd.; and "FCA-061L" (hydrogenated polybutadiene skeleton epoxy resin) manufactured by Nagase ChemteX Corporation. Specific examples of polybutadiene resins include hydroxyl-terminated polybutadiene, linear polyimides made from diisocyanate compounds and tetrabasic acid anhydrides (polyimides described in JP 2006-37083 A and WO 2008 / 153208 A), and phenolic hydroxyl-containing butadiene. The content of the butadiene structure in the polyimide resin is preferably 60% by mass to 95% by mass, more preferably 75% by mass to 85% by mass. For details of the polyimide resin, refer to the descriptions in JP 2006-37083 A and WO 2008 / 153208 A, the contents of which are incorporated herein by reference.

[0116] Another example of an elastomer is a resin containing a poly(meth)acrylate structure. A resin containing a poly(meth)acrylate structure is sometimes called a "poly(meth)acrylic resin." Examples of poly(meth)acrylic resins include Teisan Resin manufactured by Nagase ChemteX Corporation, "ME-2000," "W-116.3," "W-197C," "KG-25," and "KG-3000" manufactured by Negami Chemical Industries, and "ARUFON UH-2000" manufactured by Toagosei Co., Ltd.

[0117] Further examples of elastomers include resins containing a polycarbonate structure. Resins containing a polycarbonate structure are sometimes called "polycarbonate resins". Examples of polycarbonate resins include "FPC0220" and "FPC2136" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diols) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diols) manufactured by Kuraray Co., Ltd. In addition, linear polyimides made from hydroxyl-terminated polycarbonate, diisocyanate compounds, and tetrabasic acid anhydrides may be used. The content of carbonate structures in the polyimide resin is preferably 60% by mass to 95% by mass, more preferably 75% by mass to 85% by mass. For details of the polyimide resin, refer to the description in International Publication No. 2016 / 129541, the contents of which are incorporated herein by reference.

[0118] Another example of the elastomer is a resin containing a polysiloxane structure. A resin containing a polysiloxane structure is sometimes called a "siloxane resin." Examples of the siloxane resin include "SMP-2006," "SMP-2003PGMEA," and "SMP-5005PGMEA" manufactured by Shin-Etsu Silicone Co., Ltd., and linear polyimides made from amine-terminated polysiloxane and tetrabasic acid anhydride (see International Publication No. 2010 / 053185, JP 2002-12667 A, JP 2000-319386 A, etc.).

[0119] Further examples of elastomers include resins containing a polyalkylene structure or a polyalkyleneoxy structure. A resin containing a polyalkylene structure may be called an "alkylene resin", and a resin containing a polyalkyleneoxy structure may be called an "alkyleneoxy resin". The number of carbon atoms in the polyalkylene structure and the polyalkyleneoxy structure is preferably 2 to 15, more preferably 3 to 10, and even more preferably 5 to 8. Specific examples of alkylene resins and alkyleneoxy resins include "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation, and "BMI-3000" manufactured by Designer Molecules.

[0120] Another example of an elastomer is a resin containing a polyisoprene structure. A resin containing a polyisoprene structure is sometimes called an "isoprene resin." Specific examples of isoprene resins include "KL-610" and "KL613" manufactured by Kuraray Co., Ltd.

[0121] Yet another example of an elastomer is a resin containing a polyisobutylene structure. A resin containing a polyisobutylene structure is sometimes called an "isobutylene resin." Specific examples of isobutylene resins include Kaneka Corporation's "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer).

[0122] Another example of the elastomer is a resin containing a polystyrene structure. A resin containing a polystyrene structure is sometimes called a "styrene resin". The styrene resin may be a copolymer containing an arbitrary repeating unit other than the styrene unit in combination with the styrene unit, or may be a hydrogenated polystyrene resin. Examples of the styrene resin include styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-butadiene-butylene-styrene block copolymer (SBBS), styrene-butadiene diblock copolymer, hydrogenated styrene-butadiene block copolymer, hydrogenated styrene-isoprene block copolymer, hydrogenated styrene-butadiene random copolymer, and styrene-maleic anhydride copolymer. Specific examples of styrene resins include hydrogenated styrene-based thermoplastic elastomers "H1041", "Tuftec H1043", "Tuftec P2000", and "Tuftec MP10" (manufactured by Asahi Kasei Corporation); epoxidized styrene-butadiene thermoplastic elastomers "Epofriend AT501" and "CT310" (manufactured by Daicel Corporation); modified styrene-based elastomers having hydroxyl groups "Septon HG252" (manufactured by Kuraray Co., Ltd.); modified styrene-based elastomers having carboxyl groups "Tuftec N503M", modified styrene-based elastomers having amino groups "Tuftec N501", modified styrene-based elastomers having acid anhydride groups "Tuftec M1913" (manufactured by Asahi Kasei Chemicals Corporation); unmodified styrene-based elastomers "Septon S8104" (manufactured by Kuraray Co., Ltd.); styrene-ethylene / butylene-styrene block copolymers "FG1924" (manufactured by Kraton Corporation), and "EF-40" (manufactured by CRAY VALLEY Co., Ltd.).

[0123] From the viewpoint of obtaining the effects of the present invention prominently, the content of the elastomer is preferably 1 mass% or more, more preferably 5 mass% or more, and even more preferably 10 mass% or more, relative to 100 mass% of the non-volatile components in the resin composition, and is preferably 40 mass% or less, more preferably 35 mass% or less, and even more preferably 30 mass% or less.

[0124] From the viewpoint of obtaining the desired effect of the present invention remarkably, the content of the (B) thermoplastic resin is 10% by mass or less, preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. The lower limit is preferably 0% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more.

[0125] <(C) Inorganic filler> The resin composition may further contain an inorganic filler (C) as an optional component in addition to the above-mentioned components (A) and (B).

[0126] (C) An inorganic compound is used as the material of the inorganic filler. (C) Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The (C) inorganic filler may be used alone or in combination of two or more kinds in any ratio.

[0127] (C) Commercially available inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellfiers" and "MGH-005" manufactured by Pacific Cement Corporation; and "Sferique" and "BA-1" manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0128] (C) The inorganic filler may be a biomass-derived inorganic filler. It is preferable that the biomass-derived inorganic filler is produced from a plant raw material. For example, plants of the Equisetaceae and Poaceae families have the property of absorbing and accumulating silicon components from the ground. Therefore, by burning these plants, silica can be produced as combustion ash (Patent Publication No. 6389349). The biomass-derived inorganic filler may be a commercially available product. An example of a commercially available biomass-derived inorganic filler is "Ethical Silica" manufactured by MIT, which is a biomass silica produced from rice husks.

[0129] The average particle size of the (C) inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, even more preferably 2 μm or less, and particularly preferably 1.5 μm or less. The lower limit of the average particle size of the (C) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. The average particle size of the (C) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0130] The specific surface area of ​​the (C) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of ​​the inorganic filler (C) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, and even more preferably 30m 2 / g or less, particularly preferably 10m 2 The specific surface area of ​​the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0131] (C) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include a fluorine-containing silane coupling agent, an aminosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a silane coupling agent, an alkoxysilane, an organosilazane compound, and a titanate coupling agent. The surface treatment agent may be used alone or in any combination of two or more.

[0132] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0133] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.

[0134] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0135] (C) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0136] From the viewpoint of achieving a remarkable effect of the present invention, the content of the (C) inorganic filler is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, and is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0137] <(D) Other Additives> The resin composition may further contain other additives as optional components in addition to the above-mentioned components. Examples of such additives include thickeners, defoamers, leveling agents, adhesion promoters, flame retardants, etc. These may be used alone or in combination of two or more at any ratio.

[0138] The liquid resin in the resin component is preferably contained in the component (A) and the component (B). From the viewpoint of obtaining the effects of the present invention significantly, the liquid resin is preferably contained in the thermosetting resin (A), more preferably contained in any one of the epoxy resin (A-1), the curing agent (A-2), and the radical polymerizable resin (A-3), and further preferably contained in any one of the epoxy resin (A-1) and the curing agent (A-2).

[0139] The total content of the liquid resin in the resin composition is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, and is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on 100% by mass of the nonvolatile components in the resin composition, from the viewpoint of obtaining the effects of the present invention significantly. Also, the total content of the liquid resin in the (A) component and the (B) component is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, and is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on 100% by mass of the nonvolatile components in the resin composition, from the viewpoint of obtaining the effects of the present invention significantly.

[0140] From the viewpoint of obtaining the effects of the present invention remarkably, the biomass ratio of the resin composition is preferably 1 mass% or more, more preferably 3 mass% or more, and further preferably 5 mass% or more. The biomass ratio can be calculated by the method described in the examples below.

[0141] The resin composition can be produced, for example, by mixing the above-mentioned components in any order. In addition, in the process of mixing each component, heating and / or cooling may be performed by appropriately adjusting the temperature. In addition, during or after mixing of each component, stirring may be performed using a stirring device such as a mixer to uniformly disperse each component. Furthermore, if necessary, the resin composition may be subjected to a degassing treatment.

[0142] <Physical properties and applications of resin compositions> In the resin composition of the present invention, the contents of the (A) component and the (B) component are adjusted to be 10% by mass or more and 10% by mass or less, respectively, when the non-volatile components in the resin composition are taken as 100% by mass, and the (A) component and the (B) component are adjusted so that the biomass ratio of the liquid resin in the resin component is 40% by mass or less. Therefore, even if the biomass ratio of the resin component is increased to 5% by mass or more, it is possible to obtain a cured product with high peel strength and excellent insulation reliability. Thus, the resin composition exhibits the characteristic of having a high biomass ratio. The biomass ratio of the resin composition is preferably 1% by mass or more, more preferably 1.5% by mass or more. The upper limit is not particularly limited, but may be 100% or less. The biomass ratio can be measured according to the method described in the examples described below.

[0143] In the resin composition of the present invention, the contents of the (A) component and the (B) component are adjusted to be 10% by mass or more and 10% by mass or less, respectively, when the non-volatile components in the resin composition are taken as 100% by mass, and the (A) component and the (B) component are adjusted so that the biomass ratio of the liquid resin in the resin component is 40% by mass or less, so that the cured product thereof exhibits a characteristic of excellent peel strength between the resin composition and a conductor layer such as a copper foil. Specifically, a resin varnish is applied onto a copper foil to form a resin composition layer on the copper foil. The resin composition is cured to obtain a sample having a cured product of the resin composition layer on the copper foil. The peel strength is measured using this sample. At this time, the peel strength is preferably 0.3 kgf / cm or more, more preferably 0.4 kgf / cm or more, and even more preferably 0.5 kgf / cm or more. The upper limit is not particularly limited, but may be 10 kgf / cm or less. The peel strength between the copper foil and the copper foil can be measured according to the method described in the examples below.

[0144] In the resin composition of the present invention, the contents of the (A) component and the (B) component are adjusted to be 10% by mass or more and 10% by mass or less, respectively, when the non-volatile components in the resin composition are taken as 100% by mass, and the (A) component and the (B) component are adjusted so that the biomass ratio of the liquid resin in the resin component is 40% by mass or less, so that the cured product exhibits excellent peel strength between the plated conductor layer. Specifically, after the resin composition is cured, the cured resin composition is roughened. The roughened surface is copper plated to form a conductor layer on the cured resin composition to obtain a sample. The peel strength is measured using this sample. At this time, the peel strength is preferably 0.2 kgf / cm or more, more preferably 0.3 kgf / cm or more, and even more preferably 0.4 kgf / cm or more. The upper limit is not particularly limited, but may be 10 kgf / cm or less. The peel strength between the plated conductor layer can be measured according to the method described in the examples below.

[0145] In the resin composition of the present invention, the contents of the (A) component and the (B) component are adjusted to be 10% by mass or more and 10% by mass or less, respectively, when the non-volatile components in the resin composition are taken as 100% by mass, and the (A) component and the (B) component are adjusted so that the biomass ratio of the liquid resin in the resin components is 40% by mass or less, so that the cured product exhibits excellent insulation reliability. Specifically, the resin composition is laminated on a polyimide film on which a comb-shaped electrode is formed, and the resin composition is cured to obtain a sample. The insulation resistance value is measured using this sample. At this time, the insulation resistance value is preferably 1.0×10 8 Ω or more. There is no particular upper limit, but it is 1.0×10 20 The insulation reliability can be measured according to the method described in the examples below.

[0146] The resin composition of the present invention usually exhibits excellent lamination properties. Specifically, the resin composition is laminated on a glass cloth-based epoxy resin double-sided copper-clad laminate conductor having a comb-tooth conductor pattern with a conductor thickness of 35 μm, and then heat-cured to form an insulating layer. The unevenness difference between the conductor and other parts of the insulating layer is determined by a numerical value obtained using a non-contact surface roughness meter. At this time, the unevenness difference between the conductor and other parts is usually 2.0 μm or less. The lamination properties can be measured according to the method described in the examples below.

[0147] The resin composition of the present invention is suitable as a resin composition for insulating purposes, and is particularly suitable as a resin composition for forming an insulating layer. Thus, for example, the resin composition is suitable as a resin composition for forming an insulating layer of a printed wiring board (resin composition for forming an insulating layer of a printed wiring board). The resin composition is suitable as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for forming an interlayer insulating layer of a printed wiring board). In addition, the resin composition is suitable as a resin composition for forming an insulating layer for forming a conductor layer (including a rewiring layer) formed on an insulating layer (resin composition for forming an insulating layer for forming a conductor layer). The resin composition can also be used in a wide range of applications in which the resin composition can be used, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulant, a hole filling resin, a component embedding resin, a multi-chip package, a package-on-package, a wafer-level package, a panel-level package, and a system-in-package.

[0148] Furthermore, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition according to the present embodiment is also suitable as a resin composition for forming a rewiring formation layer as an insulating layer for forming a rewiring layer (resin composition for forming a rewiring formation layer) and as a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When a semiconductor chip package is manufactured, a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0149] The above-mentioned resin composition can also be used when the printed wiring board is a circuit board with built-in components.

[0150] [Resin sheet] The resin sheet of the present invention includes a support and a resin composition layer formed from the resin composition of the present invention provided on the support.

[0151] The thickness of the resin composition layer is preferably 100 μm or less, more preferably 75 μm or less, and even more preferably 50 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more.

[0152] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0153] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0154] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0155] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0156] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0157] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0158] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0159] The resin sheet can be produced, for example, by preparing a resin varnish by dissolving a resin composition in an organic solvent, applying this resin varnish onto a support using a die coater or the like, and then drying the same to form a resin composition layer.

[0160] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; and amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone. The organic solvents may be used alone or in combination of two or more.

[0161] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0162] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0163] [Printed wiring board] A printed wiring board according to one embodiment of the present invention includes an insulating layer formed of a cured product obtained by curing the above-described resin composition.

[0164] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate such that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing the resin composition layer to form an insulating layer

[0165] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the "inner layer substrate". When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0166] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (such as a SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0167] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.

[0168] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0169] After lamination, the laminated resin sheet may be smoothed under atmospheric pressure, for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0170] The support may be removed between step (I) and step (II) or after step (II).

[0171] In step (II), the resin composition layer is cured to form an insulating layer made of a cured product of the resin composition. The curing conditions for the resin composition layer are not particularly limited, and the conditions employed for forming an insulating layer of a printed wiring board may be used. The resin composition layer may be cured by irradiation with active energy rays such as ultraviolet rays, but is usually thermally cured by heating.

[0172] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, but in one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0173] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 120° C., preferably 60° C. to 115° C., more preferably 70° C. to 110° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0174] The method for producing a printed wiring board may further include the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer. When the support is removed after step (II), the removal of the support may be performed between steps (II) and (III), between steps (III) and (IV), or between steps (IV) and (V). In addition, the steps (I) to (V) of forming the insulating layer and the conductor layer may be repeated to form a multilayer wiring board, as necessary.

[0175] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0176] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0177] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0178] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0179] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0180] In one embodiment, the arithmetic mean roughness Ra of the insulating layer surface after the roughening treatment may be preferably 500 nm or less, more preferably less than 200 nm, even more preferably 100 nm or less, and even more preferably less than 100 nm. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0181] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0182] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0183] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0184] The conductor layer is preferably formed by plating. For example, the surface of the insulating layer can be plated by a semi-additive method, a full-additive method, or the like to form a conductor layer having a desired wiring pattern. From the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0185] A plating seed layer is formed on the surface of the insulating layer by electroless plating. Then, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. A metal layer is formed on the exposed plating seed layer by electrolytic plating, and the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0186] [Semiconductor Devices] A semiconductor device according to an embodiment of the present invention includes the above-mentioned printed wiring board. This semiconductor device can be manufactured using the above-mentioned printed wiring board.

[0187] Examples of the semiconductor device include various semiconductor devices used in electric appliances (eg, computers, mobile phones, digital cameras, televisions, etc.) and vehicles (eg, motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES

[0188] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, the operations described below were performed in an environment of normal temperature and pressure, unless otherwise specified.

[0189] <Synthesis Example 1: Synthesis of Thermoplastic Elastomer> In a reaction vessel, 69 g of bifunctional hydroxyl group-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl group equivalent = 1800 g / eq., biomass ratio 0 mass%), 40 g of aromatic hydrocarbon mixed solvent ("IPZOL 150" manufactured by Idemitsu Kosan Co., Ltd.), and 0.005 g of dibutyltin laurate (biomass ratio 0 mass%) were placed and mixed to dissolve uniformly. When the mixture became uniform, the temperature was raised to 60°C, and 8 g of isophorone diisocyanate ("IPDI" manufactured by Evonik Japan Co., Ltd., isocyanate group equivalent = 113 g / eq., biomass ratio 0 mass%) was added while stirring, and the reaction was carried out for about 3 hours.

[0190] Next, 23 g of cresol novolak resin (DIC "KA-1160", hydroxyl equivalent = 117 g / eq., biomass ratio 0 mass%) and 60 g of ethyl diglycol acetate (Daicel) were added to the reaction mixture, and the mixture was heated to 150°C with stirring and reacted for about 10 hours. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reaction product was cooled to room temperature. The reaction product was then filtered through a 100-mesh filter cloth to obtain a thermoplastic elastomer having a butadiene structure and a phenolic hydroxyl group (phenolic hydroxyl group-containing butadiene resin: non-volatile component 50% by mass, biomass ratio 0% by mass). The number average molecular weight of the thermoplastic elastomer was 5900, and the glass transition temperature was -7°C.

[0191] <Synthesis Example 2: Synthesis of active ester compound> In a 0.3-liter four-necked round flask equipped with a stirrer, a thermometer, a dropping funnel, and a nitrogen gas inlet, 11.4 g of dicyclopentadiene-phenol polyadduct (JFE Chemical Corporation's "J-DPP85", hydroxyl equivalent 165 g / eq.), 4.98 g of 1-naphthol, 10.0 g of 2,5-furandicarboxylic acid chloride, 0.026 g of tetra-n-butylammonium bromide, and 50 g of toluene were added, and the mixture was stirred while blowing in nitrogen gas and heated to 30°C to dissolve. 16.6 g of 25% aqueous caustic soda solution was added dropwise while being careful not to generate heat so that the temperature would eventually rise to 60°C. The time required for dropping was 15 minutes. After stirring at 60°C for another hour, 25 g of distilled water was added and stirred, and the aqueous layer was discarded. The organic layer was washed three times in the same manner. The organic layer was dried over sodium sulfate, the drying agent was filtered off, and then a part of the solvent was distilled off from the resulting solution to obtain 24.7 g of the target active ester compound containing 45% by mass of toluene. The active ester compound was as follows. n represents the number of repetitions and satisfies 0≦n≦8. [ka]

[0192] <Synthesis Example 3: Synthesis of active ester compound> In a 0.3-liter four-necked flask equipped with a stirrer, a thermometer, a dropping funnel, and a nitrogen gas inlet, 20.0 g of bisphenol A (hydroxyl equivalent: 114 g / eq.), 8.1 g of phenol, 25.0 g of 2,5-furandicarboxylic acid chloride, 0.053 g of tetra-n-butylammonium bromide, and 70 g of toluene were added, and the mixture was stirred while blowing in nitrogen gas and heated to 30°C to dissolve. 48 g of 25% aqueous caustic soda solution was added dropwise while being careful not to generate heat so that the temperature would ultimately rise to 60°C. The time required for dropping was 15 minutes. After stirring at 60°C for another hour, 25 g of distilled water was added and stirred, and the aqueous layer was discarded. The organic layer was washed three times in the same manner. The organic layer was dried over sodium sulfate, the drying agent was filtered off, and then a portion of the solvent was distilled off from the resulting solution to obtain the target active ester compound with a solid concentration of 45 mass% (number average molecular weight 917, active group equivalent weight approximately 153 g / eq., biomass ratio >99 mass%, non-volatile component ratio 45%) (wherein n represents a number in the range of 0≦n≦8). [ka]

[0193] <Synthesis Example 4: Synthesis of active ester compound> In Synthesis Example 2, 1) 4.98 g of 1-naphthol was replaced with 8.0 g of camphene-modified phenol (Yasuhara Chemical Co., Ltd.'s "YS Resin CP", hydroxyl equivalent 220 g / eq.). 2) 11.4 g of dicyclopentadiene-phenol polyadduct ("J-DPP85" manufactured by JFE Chemical Corporation, hydroxyl equivalent 165 g / eq.) was changed to 7.9 g of bisphenol A (hydroxyl equivalent 114 g / eq.). Except for the above, the same procedure as in Synthesis Example 2 was followed to obtain the target active ester compound (number average molecular weight: 1,348, active group equivalent weight: approximately 225 g / eq., biomass ratio: 88 mass%, non-volatile component ratio: 55%) (wherein n represents a number in the range of 0≦n≦8). [ka]

[0194] <Synthesis Example 5: Synthesis of active ester compound> In Synthesis Example 2, 1) 4.98 g of 1-naphthol was converted into 3.3 g of phenol. 2) 11.4 g of dicyclopentadiene-phenol polyadduct ("J-DPP85" manufactured by JFE Chemical Corporation, hydroxyl equivalent 165 g / eq.) was converted into 14 g of benzyl-modified bisphenol A (d and e are 1≦d+e≦4). Except for the above, the same procedure as in Synthesis Example 2 was followed to obtain an active ester compound (a toluene solution having a number average molecular weight of 433, an active group equivalent of approximately 217 g / eq., a biomass ratio of 71 mass% (n=1 and d+e=3), and a non-volatile component ratio of 46%) (wherein n is 0≦n≦8, and d and e are numbers within the range of 1≦d+e≦4). [ka]

[0195] <Example 1> 20 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq., biomass ratio of 0 mass%), 10 parts of bixylenol type epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent of about 194 g / eq., biomass ratio of 0 mass%), and 15 parts of naphthalene type epoxy resin ("ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent of about 332 g / eq., biomass ratio of 0 mass%) were added to 60 parts of methyl ethyl ketone (MEK), and dissolved by heating with stirring. This was cooled to room temperature to prepare an epoxy resin solution composition. To this epoxy resin solution, 5 parts of a triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", 2-methoxypropanol solution with active group equivalent of about 151 g / eq., biomass ratio of 0 mass%, and non-volatile component ratio of 50%), 30 parts of the active ester compound obtained in Synthesis Example 2 (toluene solution with active ester group equivalent of about 215 g / eq., biomass ratio of 28.4 mass%, and non-volatile component ratio of 55%), and 10 parts of a phenoxy resin (Mitsubishi Chemical Corporation's "YX7553BH30", biomass ratio of 10.5 mass%) were added. A resin varnish was prepared by mixing 8 parts of a 1:1 solution of MEK and cyclohexanone with 0 mass% biomass content and 30 mass% non-volatile content, 180 parts of biomass silica (MIT "Ethical Silica", average particle size 3.7 μm, biomass ratio 100 mass%) that had been surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM-573"), and 4 parts of an amine-based curing accelerator (4-dimethylaminopyridine (DMAP), biomass ratio 0 mass%, MEK solution with 5 mass% solids) and dispersing the mixture uniformly using a high-speed rotating mixer.

[0196] Next, the resin varnish was uniformly applied onto the release surface of a support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the thickness of the resin composition layer was 40 μm, and the resin was dried at 80 to 120°C (average 100°C) for 5 minutes to produce a resin sheet.

[0197] <Example 2> In Example 1, 1) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4 mass%, and a non-volatile component ratio of 55%) was changed from 30 parts to 15 parts. 2) The amount of phenoxy resin (Mitsubishi Chemical Corporation's "YX7553BH30", a 1:1 solution of MEK and cyclohexanone with a biomass ratio of 0% by mass and non-volatile content of 30% by mass) was changed from 8 parts to 12 parts. 3) 10 parts of cashew-benzoxazine resin (Tohoku Kako Co., Ltd. "CR-276", benzoxazine equivalent of about 341 g / eq., biomass ratio of 91.8% by mass) was used. 4) 5 parts of rubber particles (Aica Kogyo Co., Ltd.'s "Staphyloid AC3816N", biomass ratio 0% by mass) were used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0198] <Example 3> In Example 1, 1) The amount of naphthalene-type epoxy resin ("ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent: approx. 332 g / eq., biomass ratio: 0% by mass) was changed from 15 parts to 10 parts. 2) 5 parts of dicyclopentadiene type epoxy resin (DIC Corporation "HP7200HH", epoxy equivalent of about 283g / eq., biomass ratio 0% by mass) was used. 3) The amount of triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of approximately 151 g / eq., biomass ratio 0 mass%, non-volatile content ratio 50% in 2-methoxypropanol solution) was changed from 5 parts to 3 parts. 4) 1 part of naphthol-type hardener (Nippon Steel Chemical & Material Co., Ltd. "SN-485", hydroxyl equivalent of approximately 205 g / eq., biomass ratio 0% by mass) was used. 5) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4% by mass, and a non-volatile component ratio of 55%) was changed from 30 parts to 15 parts. 6) The amount of biomass silica (MIT's "Ethical Silica", average particle size 3.7 μm, biomass ratio 100% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was changed from 180 parts to 40 parts. 7) 140 parts of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm, biomass ratio 0 mass%) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was used. 8) 10 parts of cashew-benzoxazine resin (Tohoku Kako Co., Ltd. "CR-276", benzoxazine equivalent of about 341 g / eq., biomass ratio of 91.8% by mass) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0199] <Example 4> In Example 1, 1) The amount of naphthalene-type epoxy resin ("ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent: approx. 332 g / eq., biomass ratio: 0% by mass) was changed from 15 parts to 10 parts. 2) 5 parts of phenolphthalimidine type epoxy resin ("WHR-991S" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of approximately 265 g / eq., biomass ratio of 0% by mass) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0200] <Example 5> 8 parts of bisphenol A type epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent about 180g / eq., biomass ratio 0 mass%), 20 parts of biphenyl type epoxy resin (Nippon Kayaku Co., Ltd. "NC3000L", epoxy equivalent about 269g / eq., biomass ratio 0 mass%), 15 parts of naphthalene type epoxy resin (Nippon Steel Chemical & Material Co., Ltd. "ESN475V", epoxy equivalent about 332g / eq., biomass ratio 0 mass%), 2 parts of epoxidized cardanol resin (Tohoku Kako Co., Ltd. "FE-5130", epoxy equivalent about 342g / eq., biomass ratio 83.3 mass%) were added to 40 parts of methyl ethyl ketone (MEK), and dissolved by heating with stirring. This was cooled to room temperature to prepare an epoxy resin solution composition. This epoxy resin solution composition was mixed with 10 parts of cash-benzoxazine resin ("CR-276" manufactured by Tohoku Kako Co., Ltd., benzoxazine equivalent of about 341 g / eq., biomass ratio of 91.8 mass%), 4 parts of a phenolic hardener containing a triazine skeleton ("LA-3018-50P" manufactured by DIC Corporation, active group equivalent of about 151 g / eq., biomass ratio of 0 mass%, non-volatile component ratio of 50% in 2-methoxypropanol solution), 2 parts of a phenolic hardener derived from a natural product (Resveratrol, phenol equivalent of about 76 g / eq., biomass ratio of 100 mass%), and the active ester compound obtained in Synthesis Example 2 (active ester group equivalent of about 215 g / eq., biomass ratio of 91.8 mass%). A resin varnish was prepared by mixing 40 parts of a toluene solution with a biomass ratio of 28.4% and a non-volatile content of 55%, 8 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a biomass ratio of 0% and a non-volatile content of 30% by weight), 55 parts of spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm, biomass ratio of 0% by weight) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.), and 4 parts of an amine-based curing accelerator (4-dimethylaminopyridine (DMAP), a MEK solution with a biomass ratio of 0% by weight and a solid content of 5% by weight). The mixture was uniformly dispersed using a high-speed rotating mixer.

[0201] Next, the resin varnish was uniformly applied onto the release surface of a support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the thickness of the resin composition layer was 40 μm, and the resin was dried at 80 to 120°C (average 100°C) for 5 minutes to produce a resin sheet.

[0202] <Example 6> In Example 5, Two parts of a naturally derived phenolic hardener (Resveratrol, phenol equivalent of approximately 76 g / eq., biomass ratio of 100% by mass) were replaced with two parts of a naturally derived phenolic hardener (Curcumin, phenol equivalent of approximately 184 g / eq., biomass ratio of 100% by mass). A resin varnish and a resin sheet were prepared in the same manner as in Example 5 except for the above.

[0203] <Example 7> In Example 2, 1) 10 parts of bixylenol type epoxy resin (Mitsubishi Chemical Corporation's "YX4000HK", epoxy equivalent of about 194 g / eq., biomass ratio of 0 mass%) was replaced with 8 parts of epoxidized soybean oil (New Japan Chemical Co., Ltd.'s "Sanso Cizer E-2000H", epoxy equivalent of about 234 g / eq., biomass ratio of 93.2 mass%). 2) 5 parts of rubber particles (Aica Kogyo's "Staphyloid AC3816N", biomass ratio 0% by mass) were replaced with 3 parts of thermoplastic polyamide resin (Tsukuno Foods Co., Ltd.'s "Vegichem Green V335", biomass ratio 80% by mass), 3) 12 parts of phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a biomass ratio of 0 mass% and a non-volatile content of 30 mass%) was not used. A resin varnish and a resin sheet were prepared in the same manner as in Example 2 except for the above.

[0204] <Example 8> In Example 7, 8 parts of epoxidized soybean oil ("Sanso Cizer E-2000H" manufactured by New Japan Chemical Co., Ltd., epoxy equivalent of about 234 g / eq., biomass ratio of 93.2 mass%) were changed to 6 parts of glycerin acrylate ("Aronix M-930" manufactured by Toa Gosei Co., Ltd., biomass ratio of 35 mass%) and 2 parts of a liquid resin derived from natural products ("β-carotene", biomass ratio of 100 mass%). A resin varnish and a resin sheet were prepared in the same manner as in Example 7 except for the above.

[0205] <Example 9> 10 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq., biomass ratio of 0 mass%), 10 parts of naphthylene ether type epoxy resin ("HP-6000" manufactured by DIC Corporation, epoxy equivalent of about 250 g / eq., biomass ratio of 0 mass%), 15 parts of cashew modified epoxy resin ("LITE 514SE" manufactured by Cardolite Co., Ltd., epoxy equivalent of about 401 g / eq., biomass ratio of 91.7 mass%), 20 parts of methyl ethyl ketone (MEK), and 30 parts of 1-methoxy-2-propanol were added and heated and dissolved while stirring. This was cooled to room temperature to prepare an epoxy resin dissolved composition. To this epoxy resin solution, 2 parts of a triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", 2-methoxypropanol solution with active group equivalent of about 151 g / eq., biomass ratio of 0 mass%, and non-volatile content ratio of 50%), 10 parts of the active ester compound obtained in Synthesis Example 2 (toluene solution with active ester group equivalent of about 215 g / eq., biomass ratio of 28.4 mass%, and non-volatile content ratio of 55%), 10 parts of a cashew-modified phenolic resin (Sumitomo Bakelite Co., Ltd.'s "PR-12686F", active group equivalent of about 142 g / eq., biomass ratio of about 30 mass%), 2 parts of a shellac resin (Koyo Chemical Co., Ltd.'s "KL-1001", biomass ratio of 100 mass%), tannic acid (Sumitomo Pharma Food & Chemical Co., Ltd.'s "Bakelite" One part of biomass silica (100% by mass), 3 parts of thermoplastic polyamide resin ("Vegichem Green V335" manufactured by Tsuno Food Industry Co., Ltd., biomass ratio 80% by mass), 140 parts of biomass silica ("Ethical Silica" manufactured by MIT, average particle size 3.7 μm, biomass ratio 100% by mass) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.), 2 parts of amine-based hardening accelerator (4-dimethylaminopyridine (DMAP), biomass ratio 0% by mass, MEK solution with solid content of 5% by mass), and 1 part of imidazole-based hardening accelerator ("1B2PZ" manufactured by Shikoku Chemical Industry Co., Ltd., 1-benzyl-2-phenylimidazole, MEK solution with solid content of 10% by mass) were mixed and uniformly dispersed using a high-speed rotating mixer to prepare a resin varnish.

[0206] A resin varnish was uniformly applied onto the release surface of a support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the thickness of the resin composition layer was 40 μm, and the resin sheet was produced by drying at 80 to 120°C (average 100°C) for 8 minutes.

[0207] <Example 10> 5 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq., biomass ratio of 0 mass%), 10 parts of naphthylene ether type epoxy resin ("HP-6000" manufactured by DIC Corporation, epoxy equivalent of about 250 g / eq., biomass ratio of 0 mass%), 5 parts of aliphatic epoxy resin ("Denacol EX-521" manufactured by Nagase ChemteX Corporation, epoxy equivalent of 183 g / eq., biomass ratio of 50 mass%) were added to 55 parts of methyl ethyl ketone (MEK), and dissolved by heating with stirring. This was cooled to room temperature to prepare an epoxy resin dissolved composition. This epoxy resin solution composition was mixed with 5 parts of cash-benzoxazine resin (Tohoku Kako Co., Ltd. "CR-276", benzoxazine equivalent of about 341 g / eq., biomass ratio of 91.8 mass%), 40 parts of the thermoplastic elastomer obtained in Synthesis Example 1 (solid concentration of 50 mass%, biomass ratio of 0 mass%), 50 parts of biomass silica (MIT Co., Ltd. "Ethical Silica", average particle size 3.7 μm, biomass ratio of 100 mass%) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM-573"), and 4 parts of an imidazole-based curing accelerator (Shikoku Kasei Kogyo Co., Ltd. "1B2PZ", 1-benzyl-2-phenylimidazole, MEK solution with a solid content of 10 mass%), and uniformly dispersed with a high-speed rotating mixer to prepare a resin varnish.

[0208] A resin varnish was uniformly applied onto the release surface of a support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the resin composition layer had a thickness of 40 μm, and the resin sheet was produced by drying at 80 to 120°C (average 100°C) for 5 minutes.

[0209] <Example 11> In Example 1, 1) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4% by mass, and a non-volatile component ratio of 55%) was changed from 30 parts to 20 parts. 2) 12 parts of the active ester compound obtained in Synthesis Example 3 (active group equivalent: approximately 153 g / eq., biomass ratio >99% by mass, non-volatile component ratio 45%) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0210] <Example 12> In Example 1, 1) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4% by mass, and a non-volatile component ratio of 55%) was changed from 30 parts to 20 parts. 2) 10 parts of the active ester compound obtained in Synthesis Example 4 (active group equivalent: approximately 225 g / eq., biomass ratio: 88% by mass, non-volatile component ratio: 55%) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0211] <Example 13> In Example 1, 1) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4% by mass, and a non-volatile component ratio of 55%) was changed from 30 parts to 20 parts. 2) 12 parts of the active ester compound obtained in Synthesis Example 5 (active group equivalent weight: approximately 217 g / eq., biomass ratio: 71 mass% (n=1 and d+e=3), non-volatile component ratio: 46% in toluene solution) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0212] <Example 14> In Example 1, 1) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4% by mass, and a non-volatile component ratio of 55%) was changed from 30 parts to 25 parts. 2) 3 parts of an active ester compound (Honshu Chemical Industry Co., Ltd.'s "BPTMC-FE", active ester group equivalent of approximately 249 g / eq., biomass ratio of 32% by mass) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0213] <Example 15> In Example 1, 1) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4% by mass, and a non-volatile component ratio of 55%) was changed from 30 parts to 25 parts. 2) 3 parts of an active ester compound ("BP-FE" manufactured by Honshu Chemical Industry Co., Ltd., active ester group equivalent of approximately 187 g / eq., biomass ratio of 45% by mass) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0214] <Example 16> In Example 1, 1) The amount of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4% by mass, and a non-volatile component ratio of 55%) was changed from 30 parts to 25 parts. 2) 3 parts of an active ester compound ("TMPBP-FE" manufactured by Honshu Chemical Industry Co., Ltd., active ester group equivalent weight approximately 217 g / eq., biomass ratio 36% by mass) was used. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0215] <Example 17> In Example 5, 1) 2 parts of epoxidized cardanol resin (Tohoku Kako "FE-5130", epoxy equivalent approximately 342 g / eq., biomass ratio 83.3 mass%) was changed to 2 parts of LIMONENE DIOXIDE (Cargill, epoxy equivalent approximately 96 g / eq., biomass ratio 100 mass%). A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0216] <Comparative Example 1> In Example 1, 1) 30 parts of the active ester compound obtained in Synthesis Example 2 (a toluene solution having an active ester group equivalent of about 215 g / eq., a biomass ratio of 28.4 mass%, and a non-volatile component ratio of 55%) was replaced with 26 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", an active ester group equivalent of about 223 g / eq., a biomass ratio of 0 mass%, and a non-volatile component ratio of 65% in toluene solution); 2) 180 parts of biomass silica (MIT's "Ethical Silica", average particle size 3.7 μm, biomass ratio 100% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was replaced with 180 parts of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm, biomass ratio 0% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573"). A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0217] <Comparative Example 2> In Comparative Example 1, 1) 180 parts of spherical silica (Admatechs' SO-C2, average particle size 0.5 μm, biomass ratio 0 mass%) surface-treated with a silane coupling agent (Shin-Etsu Chemical's KBM-573) was replaced with 50 parts of biomass silica (MIT's Ethical Silica, average particle size 3.7 μm, biomass ratio 100 mass%) surface-treated with a silane coupling agent (Shin-Etsu Chemical's KBM-573). 2) The amount of phenoxy resin (Mitsubishi Chemical Corporation's "YX7553BH30", a 1:1 solution of MEK and cyclohexanone with a biomass ratio of 0% by mass and non-volatile content of 30% by mass) was changed from 8 parts to 30 parts. 3) 8 parts of rubber particles ("Staphyloid AC3816N" manufactured by Aica Kogyo Co., Ltd., biomass ratio 0% by mass) were used. A resin varnish and a resin sheet were prepared in the same manner as in Comparative Example 1 except for the above.

[0218] <Comparative Example 3> In Comparative Example 2, 1) The amount of biphenyl-type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of approximately 269 g / eq., biomass ratio of 0 mass%) was changed from 20 parts to 8 parts. 2) The amount of triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of approximately 151 g / eq., biomass ratio 0 mass%, non-volatile content ratio 50% in 2-methoxypropanol solution) was changed from 5 parts to 2 parts. 3) The amount of biomass silica (MIT's "Ethical Silica", average particle size 3.7 μm, biomass ratio 100% by mass) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was changed from 50 parts to 80 parts. 4) The amount of phenoxy resin (Mitsubishi Chemical Corporation's "YX7553BH30", a 1:1 solution of MEK and cyclohexanone with a biomass ratio of 0% by mass and non-volatile content of 30% by mass) was changed from 30 parts to 40 parts. 5) The amount of rubber particles (Aica Kogyo's "Staphyloid AC3816N", biomass ratio 0% by mass) was changed from 8 parts to 5 parts. 6) The amount of amine-based hardening accelerator (4-dimethylaminopyridine (DMAP), MEK solution with 0% biomass and 5% solids) was changed from 4 parts to 2 parts. 7) 10 parts of bixylenol-type epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent approximately 194 g / eq., biomass ratio 0 mass%), 15 parts of naphthalene-type epoxy resin ("ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent approximately 332 g / eq., biomass ratio 0 mass%), and 26 parts of active ester compound ("HPC-8000-65T" manufactured by DIC Corporation, active ester group equivalent approximately 223 g / eq., biomass ratio 0 mass%, toluene solution with non-volatile component ratio of 65%) were not used. A resin varnish and a resin sheet were prepared in the same manner as in Comparative Example 2 except for the above.

[0219] <Comparative Example 4> In Example 7, 1) The amount of biphenyl-type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of approximately 269 g / eq., biomass ratio of 0 mass%) was changed from 20 parts to 10 parts. 2) The amount of naphthalene-type epoxy resin ("ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent of approximately 332 g / eq., biomass ratio of 0 mass%) was changed from 15 parts to 5 parts. 3) 8 parts of epoxidized soybean oil ("Sanso Cizer E-2000H" manufactured by Shin Nippon Rika Co., Ltd., epoxy equivalent of about 234 g / eq., biomass ratio of 93.2 mass%) was replaced with 20 parts of aliphatic epoxy resin ("Denacol EX-521" manufactured by Nagase ChemteX Corporation, epoxy equivalent of 183 g / eq., biomass ratio of 50 mass%). 4) 10 parts of epoxidized cardanol resin (Tohoku Kako "FE-5130", epoxy equivalent approximately 342g / eq., biomass ratio 83.3% by mass) was used. 5) Three parts of thermoplastic polyamide resin ("Vegichem Green V335" manufactured by Tsuno Foods Industries Co., Ltd., biomass ratio 80% by mass) was replaced with eight parts of phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, biomass ratio 0% by mass, 1:1 solution of MEK and cyclohexanone with non-volatile content of 30% by mass). A resin varnish and a resin sheet were prepared in the same manner as in Example 7 except for the above.

[0220] <Measurement of peel strength between copper foil> (1) Preparation of evaluation board A The resin varnish prepared in the examples, comparative examples, and reference examples was applied to a copper foil ("JDLC" manufactured by JX Metals, thickness 12 μm, 240 mm square) by a die coater so that the thickness of the resin composition layer after drying was 40 μm, and dried at 80°C to 120°C (average 100°C) for 10 minutes to obtain a resin-attached copper foil sheet. This resin-attached copper foil sheet was laminated to both sides of the laminated board so that the resin composition layer was in contact with each other using a batch-type vacuum pressure laminator (manufactured by Meiki Co., Ltd., MVLP-500). The lamination was performed by reducing the pressure for 30 seconds to a pressure of 13 hPa or less, and then pressing for 30 seconds at 100°C and a pressure of 0.74 MPa. The resin-attached copper foil sheet was laminated on the laminated board, and the resin composition layer was cured under the curing conditions of 180°C and 90 minutes to form an insulating layer. This is called "evaluation substrate A".

[0221] (2) Measurement of peel strength between copper foil A cut 10 mm wide and 100 mm long was made in the copper foil of evaluation board A, and one end of this was peeled off and held with a gripping tool (Autocom type testing machine "AC-50C-SL" manufactured by TSE Corporation). The load (kgf / cm) when 20 mm was peeled off vertically at a speed of 50 mm / min at room temperature was measured in accordance with JIS C6481.

[0222] <Measurement of plating peel strength> (1) Preparation of evaluation board B A glass cloth-based epoxy resin double-sided copper-clad laminate with copper foil on the surface (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") was prepared. The copper foil on the surface of this inner layer substrate was etched with a microetching agent (Mec "CZ8101") with a copper etching amount of 1 μm to perform a roughening treatment. After that, it was dried at 190°C for 30 minutes to produce a surface-treated inner layer substrate.

[0223] The resin sheets obtained in the examples, comparative examples, and reference examples were laminated on both sides of the substrate-treated inner layer substrate using a batch-type vacuum pressure laminator (a two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.) so that the resin composition layer was bonded to the substrate-treated inner layer substrate. This lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds. The laminated resin sheet was then heat-pressed at atmospheric pressure, 100°C, and a pressure of 0.5 MPa for 60 seconds to smooth it. This was then placed in an oven at 130°C and heated for 30 minutes, and then transferred to an oven at 170°C and heated for 30 minutes to obtain a substrate with a cured resin.

[0224] After peeling off the support from the substrate with the cured resin, the substrate was immersed in swelling dip Securigant P manufactured by Atotech Japan Co., Ltd., which is a swelling solution, at 60°C for 10 minutes. Next, the substrate was immersed in Concentrate Compact P manufactured by Atotech Japan Co., Ltd., which is a roughening solution, at 80°C for 20 minutes. Finally, the substrate was immersed in Reduction Solution Securigant P manufactured by Atotech Japan Co., Ltd., which is a neutralizing solution, at 40°C for 5 minutes. Next, the substrate was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then in an electroless copper plating solution at 25°C for 20 minutes. After heating at 150°C for 30 minutes to perform an annealing treatment, an etching resist was formed, and after pattern formation by etching, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 30 μm. Next, an annealing treatment was performed at 200°C for 60 minutes, and the obtained substrate was used as evaluation substrate B.

[0225] (2) Measurement of plating peel strength A 10 mm wide, 100 mm long cut was made in the conductor layer of evaluation board B, and one end of the cut was peeled off and held with a gripping tool (TSE Autocom type testing machine "AC-50C-SL"), and the load (kgf / cm) when 20 mm was peeled off vertically at a speed of 50 mm / min at room temperature was measured in accordance with JIS C6481.

[0226] <Evaluation of insulation reliability> (1) Preparation of laminate for insulation reliability evaluation The resin sheets obtained in the Examples, Comparative Examples, and Reference Examples were laminated on a polyimide film having a comb-tooth electrode (line / space = 15 μm / 15 μm) so that the resin composition layer of the resin sheet was in contact with the copper circuit surface of the comb-tooth electrode using a batch-type vacuum pressure laminator (MVLP-500, manufactured by Meiki Co., Ltd.). The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing for 30 seconds at 100 ° C and a pressure of 0.74 MPa. After peeling off the PET film of the support, the laminate was heat-cured at 180 ° C for 90 minutes to obtain a laminate for evaluating insulation reliability.

[0227] (2) Evaluation of insulation reliability This evaluation laminate was placed in a highly accelerated life test apparatus ("PM422" manufactured by Kusumoto Chemical Industries, Ltd.) and the insulation resistance value of the evaluation laminate after 100 hours at 130°C, 85% RH, and an applied voltage of 3.3 V was measured and evaluated according to the following criteria. 〇: Insulation resistance is 1.0×10 8 More than Ω. ×: Insulation resistance is 1.0×10 8 Less than ohms.

[0228] <Evaluation of lamination properties> The resin sheets obtained in the examples, comparative examples, and reference examples were laminated on a comb-shaped conductor pattern with a conductor thickness of 35 μm and L (line: wiring width) / S (space: interval width)=160 μm / 160 μm using a batch-type vacuum pressure laminator (MVLP-500, manufactured by Meiki Co., Ltd.). The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing for 30 seconds at 100°C and a pressure of 0.74 MPa. The resin composition was then cured at 130°C for 30 minutes, and then at 170°C for 30 minutes to form an insulating layer, after which the PET film, which was the support, was peeled off. The difference in unevenness (Rt: maximum peak-to-valley) between the conductor and other parts of the insulating layer was determined using a non-contact surface roughness meter (WYKO NT3300, manufactured by B-CO Instruments) in VSI mode with a 10x lens, with a measurement range of 1.2mm x 0.91mm, and was evaluated according to the following criteria. Good: The difference in unevenness between the conductor and other areas is 2.0 μm or less. ×: The difference in unevenness between the conductor and other areas is greater than 2.0 μm.

[0229] <Calculation of biomass ratio> The Japan Organic Resources Association defines "biomass" as any organic resource derived from a renewable organism, excluding fossil resources (however, it does include inorganic resources such as shells that are produced directly by organisms). Based on this definition, the biomass ratio of the raw materials used in the blend was calculated using the following formula. The biomass ratio in the resin component was also evaluated using the following criteria. Biomass ratio (mass%) = (weight of biological components in a substance / weight of substance) x 100

[0230] <Determination of biomass ratio in resin components> Based on the above-mentioned method for calculating the biomass ratio, the biomass ratio in the resin components excluding the inorganic filler component in the resin composition was calculated and judged according to the following criteria. ○: Biomass ratio in the resin component is 5% by mass or more ×: Biomass ratio in the resin component is less than 5% by mass

[0231] [Table 1] [Table 2] [Table 3] *In the table, the contents of components (A) to (C) indicate the contents when the total amount of non-volatile components in the resin composition is taken as 100 mass %.

Claims

1. (A) a thermosetting resin, and (B) a resin composition containing a thermoplastic resin, The component (A) contains an epoxy resin (A-1), The component (A-1) contains a solid epoxy resin and a liquid epoxy resin, The content of the component (A) is 10% by mass or more when the total amount of non-volatile components in the resin composition is 100% by mass, the content of the liquid epoxy resin contained in the component (A-1) is 10% by mass or less, relative to 100% by mass of the non-volatile components in the resin composition; The content of the (B) component is 10% by mass or less when the total amount of non-volatile components in the resin composition is 100% by mass, The biomass ratio of the resin component in the resin composition is 5.5% by mass or more, A resin composition, wherein a biomass ratio of a liquid resin in a resin component is 40 mass% or less.

2. The resin composition according to claim 1 , further comprising (C) an inorganic filler.

3. The resin composition according to claim 2, wherein the content of the inorganic filler (C) is 20% by mass or more when the nonvolatile components in the resin composition are taken as 100% by mass.

4. The resin composition according to claim 1, wherein the thermosetting resin (A) contains a curing agent (A-2).

5. The resin composition according to claim 1, wherein the liquid resin contains either (A-1) an epoxy resin or (A-2) a curing agent.

6. The resin composition according to claim 1 , which is for forming an insulating layer.

7. A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of claims 1 to 6.

8. A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of claims 1 to 6.

9. A semiconductor device comprising the printed wiring board according to claim 8.

Citation Information

Patent Citations

  • Laminated base material for printed circuit board, laminated body for printed circuit board, printed circuit board, and semiconductor device

    JP2016056371A

  • Photosensitive resin composition, photosensitive element, and printed wiring board and method for manufacturing the same

    JP2019066792A

  • Resin composition, molded body, and method for producing resin composition

    JP2019157028A

  • Epoxy resin composition, prepreg including the same, and fiber-reinforced plastic

    JP2022147485A

  • Sealing film, sealed structure, and method for manufacturing sealed structure

    WO2018199306A1